Aplikasi Trichoderma sp. pada Media Kombinasi Ampas Tebu dan Serbuk Gergaji dalam Rangka Peningkatan Produksi Jamur Tiram Putih (Pleurotus ostreatus) - Dwi Novidiani; Rahmi Zulhidiani; Anna Maria Makalew (Agroekotek View, 2018)
White oyster mushrooms are considered healthy food groups, because white oyster mushrooms have been cultivated almost all ingredients not using chemical fertilizers and pesticides. Sawdust often used as a medium of white oyster mushroom growth and also excess waste bagasse can be used and used for the cultivation of white oyster mushrooms. this paper is part of a major study that on this limit has the purpose of knowing the effect of bagasse and wood powder on the growth of white oyster mushroom. through a randomized block design with 2 nested factorials with 3 replications of the results. That this paper is written from the research section with the type medium 100% sawdust, 50% sawdust + 50% bagasse and 100% bagasse to be the best medium in the production of white oyster mushroom is the type of media 50% sawdust + 50% bagasse gives a real effect on the first time the appearance of the fruit body, the age of the first harvest of white oyster mushrooms, and the wet weight of white oyster mushroom fruit body but not affecting against the time of mycelium growth and the timing of the complete mycelium dissemination